Biomimetic Nanostructures Fabricated by Nanoimprint Lithography for Improved Cell‐Coupling. (6th September 2020) - Nowduri, Bharat; Schulte, Steven; Decker, Dominique; Schäfer, Karl‐Herbert; Saumer, Monika
Abstract: Since the advent of biosensing, structuring of electrode surfaces for the improvement of cell‐coupling and electrophysiological properties has been extensively investigated. Most of these methods result in structures with predefined dimensions and regular organization. Nevertheless, natural adhesion surfaces of the cells are hardly uniform. Therefore, this study focusses on fabricating randomly organized nanostructures mimicking the irregular distribution of natural collagen fibers coated on a planar surface. Fiber geometries are replicated by using a spin‐coating process followed by thermal nanoimprint lithography and gold electroplating. Microscopic studies reveal the width of these biomimetic collagen‐like gold nanostructures ranging between 200 nm and 5 µm, with a uniform height of ≈35 nm. In comparison to unstructured gold surfaces, nanostructured surfaces display a decrease in impedance magnitude by 50% for frequencies below 1 kHz and show an increase in critical free surface energy by 35%, the latter translating to an increased surface wettability. Culturing enteric neurons from postnatal mice, a relative hard to handle type of neurons, results in an improved spreading of the neural networks on the nanostructured surfaces. Abstract : Biomimetic nanostructures fabricated via nanoimprint lithography and subsequent electroplating is a novel structuring technique, which combines the advantages of artificial durable materials with biophysical properties of natural biomolecules. These artificial biomimetic structures not only improve the surface properties and cell coupling, but also have the inherent advantage of being reproducible in comparison to natural nanostructures.